Limitations on the Use of Social Media in Health Services in Terms of Legislation - Tengku Keizerina Devi Azwar; Utary Maharany Barus; Montayana Meher; Hilbertus Sumplisius M. Wau (Faculty of Law, Universitas Pekalongan, 2025)
Activities on social media have become a habit that isdifficult for users to leave behind, making theseactivities take place continuously in order to continueto exist on social media. But not all of these activitiesare beneficial, they can also be disastrous for users andeven other people. The urgency of this study is to focuson the limits of the use of social media in health careactivities, which will see and know the rules governingthe limits of the use of social media during health careactivities. Reviewing whether the activity of recordinghealth service activities is justified by law so that itwill not interfere with health service activities. Thisstudy uses normative law which is descriptiveanalytical, using a comparative law and case approach.The data source uses secondary data sources, consistingof primary legal materials, secondary legal materials,and tertiary legal materials. Data collection usesliterature collection techniques with data collectiontools in the form of document studies and legislation,with data analysis using qualitative research. Thisstudy concludes that in Indonesia, activities on socialmedia have not yet been regulated, making it difficultfor justice seekers to gain access if there is abuse ofactivities on social media, especially when providinghealth services